Worsening and newly diagnosed paraneoplastic syndromes following anti-PD-1 or anti-PD-L1 immunotherapies, a descriptive study. Issue 1 (3rd December 2019) - Manson, Guillaume; Maria, Alexandre Thibault Jacques; Poizeau, Florence; Danlos, François-Xavier; Kostine, Marie; Brosseau, Solenn; Aspeslagh, Sandrine; Du Rusquec, Pauline; Roger, Maxime; Pallix-Guyot, Maud; Ruivard, Marc; Dousset, Léa; et al.
Abstract : Background: Paraneoplastic syndromes (PNS) are autoimmune disorders specifically associated with cancer. There are few data on anti-PD-1 or anti-PD-L1 immunotherapy in patients with a PNS. Our objective was to describe the outcome for patients with a pre-existing or newly diagnosed PNS following the initiation of anti-PD-1 or anti-PD-L1 immunotherapy. Methods: We included all adult patients (aged ≥18) treated with anti-PD-1 or anti-PD-L1 immunotherapy for a solid tumor, diagnosed with a PNS, and registered in French pharmacovigilance databases. Patients were allocated to cohorts 1 and 2 if the PNS had been diagnosed before vs. after the initiation of immunotherapy, respectively. Findings: Of the 1304 adult patients screened between June 27th, 2014, and January 2nd, 2019, 32 (2.45%) had a PNS and were allocated to either cohort 1 ( n  = 16) or cohort 2 ( n  = 16). The median (range) age was 64 (45–88). The tumor types were non-small-cell lung cancer ( n  = 15, 47%), melanoma ( n  = 6, 19%), renal carcinoma ( n  = 3, 9%), and other malignancies ( n  = 8, 25%). Eleven (34%) patients presented with a neurologic PNS, nine (28%) had a rheumatologic PNS, eight (25%) had a connective tissue PNS, and four (13%) had other types of PNS. The highest severity grade for the PNS was 1–2 in 10 patients (31%) and ≥ 3 in 22 patients (69%). Four patients (13%) died as a result of the progression of a neurologic PNS (encephalitis in three cases, and Lambert-Eaton syndrome in one case). Following the initiation of immunotherapy, the PNS symptoms worsened in eight (50%) of the 16 patients in cohort 1. Interpretation: Our results show that PNSs tend to be worsened or revealed by anti-PD-1 or anti-PD-L1 immunotherapy. Cases of paraneoplastic encephalitis are of notable concern, in view of their severity. When initiating immunotherapy, physicians should carefully monitor patients with a pre-existing PNS.